A percepção da paisagem literária em Alumbramentos, de Maria Lúcia Dal Farra - Marin, Neilisa Moreira (2017)
This study aims to describe the theory of the literary landscape proposed by Michel Collot (2013), and to analyze it in some of the poems contained in Alumbramentos (2011), by Maria Lúcia Dal Farra. It is known that the poetry of Dal Farra has aroused the interest of scholars and researchers for the perception of the landscape in his work, whose raw material may consist of a new design on the poetic making, both in its forms of production and reception. In this work, the literary landscape is understood as the "being in the world" through writing, a principle instituted by the teacher, researcher and essayist Michel Collot (2013), whose main title, Poetics and Philoso phy of Landscape (2013) The great theoretical contribution to this study. The analysis of the selected poems showed that, from the recurrence to certain thematic axes, the landscape is inscribed based on three notions at the same time distinct and inseparable: alterity, intercorporeidade, structures of poetic creation and lyrical emotion, once That the so-called landscape phenomenon is constituted through language.